Synchrotron radiation of relativistic electrons moving at small pitch-angles in inhomogeneous magnetic field - Sobolev, Ya.M. (Вопросы атомной науки и техники, 2006)
Synchrotron radiation of relativistic electrons moving in an inhomogeneous magnetic field at small pitch-angles
is considered. The trajectory of an ultrarelativistic electron is obtained taking into account a curvature and radial
inhomogeneity of magnetic field lines. The general formulae describing the radiation of an electron moving at pitchangles
from 0 to π/2 are derived. The range of instantaneous characteristic frequencies appears instead a single
characteristic frequency. The applicability of the formulae for runaway electrons in the tokamak is evaluated. The
condition for using of the obtained formulae is derived. Рассмотрено синхротронное излучение релятивистских электронов, движущихся под малыми питч-
углами в неоднородном магнитном поле. Траектория ультрарелятивистского электрона получена с учетом
кривизны и радиальной неоднородности линий магнитного поля. Выведены общие формулы, описывающие
излучение электрона, движущегося при питч-углах от 0 до π/2. Вместо отдельной характерной частоты
возникает область характеристических частот. Оценена применимость формул для убегающих электронов в
токамаке. Выведены условия для использования полученных формул. Розглянуте синхротронне випромінювання релятивістських електронів, що рухаються під малими пітч-
кутами у неоднорідному магнітному полі. Траєкторія ультрарелятивістського електрона отримана з
урахуванням кривизни і радіальної неоднорідності ліній магнітного поля. Виведені загальні формули, які
описують випромінювання електрона, що рухається при пітч-кутах від 0 до π/2. Замість окремої характерної
частоти виникає область характеристичних частот. Проведена оцінка застосовності формул для збігаючих
електронів у токамаці. Виведені умови для застосування отриманих формул.